Level of aggression and empathy depending on demographic status of probands and their parents - Атраментова, Л. О.; Лучко, К. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The article contains the results of population genetics analysis of connection of aggression and empathy and demographic status of probands and their parents. It has been set that the level of aggression for migrants is higher (41,7 points), than for natives (36,3 points), the level of empathy for migrants is lower (3,2 points), than for natives (5,5 points). The least «aggressive» among the native probands were those whose parents as indigenous (38.7 points), and the level of empathy is highest (5.4 points). The most «aggressive» among native probands were those whose parents are migrants: aggression – 40,6 points, empathy – 5,0 points. Probands-migrants whose both parents were born in Kharkiv, showed minimum average aggression (39,8 points) and minimum of empathy (4,9 points).